2003
DOI: 10.1046/j.1471-4159.2003.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Tethering the N‐terminus of the prion protein compromises the cellular response to oxidative stress

Abstract: The role of the N-terminal half of the prion protein (PrP C ) in normal cellular function and pathology remains enigmatic. To investigate the biological role of the N-terminus of PrP, we examined the cellular properties of a construct of murine PrP, PrP-DA, in which the N-terminus is tethered to the membrane by an uncleaved signal peptide and which retains the glycosylphosphatidylinositol anchor. Human neuroblastoma SH-SY5Y cells expressing PrP-DA were more susceptible to hydrogen peroxide and copper induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 44 publications
5
59
0
Order By: Relevance
“…These findings suggest that PrP C participates in the modulation of the activity of these enzymes and/or PrP C itself functions as an antioxidant molecule. Moreover, it has been reported that the flexible N-terminal domain of PrP C , which we have shown contains heminbinding sites, is influential in cellular responses to oxidative stress (50,51). This suggests that the peroxidase activity of hemin-PrP C complexes may play a protective role against oxidative stress.…”
Section: Discussionsupporting
confidence: 51%
“…These findings suggest that PrP C participates in the modulation of the activity of these enzymes and/or PrP C itself functions as an antioxidant molecule. Moreover, it has been reported that the flexible N-terminal domain of PrP C , which we have shown contains heminbinding sites, is influential in cellular responses to oxidative stress (50,51). This suggests that the peroxidase activity of hemin-PrP C complexes may play a protective role against oxidative stress.…”
Section: Discussionsupporting
confidence: 51%
“…The residence of PrP C within lipid rafts and the number of reported binding partners in this topographical context support the likely importance of these specialized plasmalemma microdomains in the cellular biology of the prion protein (4,52). Much less explored has been the role of non-lipid raft domains, a consideration underscored by the endogenous trafficking and internalization route followed by PrP C , especially in response to complexing of copper.…”
Section: Discussionmentioning
confidence: 90%
“…Endoproteolytic cleavage of PrP C could occur at some point along this pathway and facilitate binding of liberated fragments to phosphatidylserine, but the absence of proteolysis may not preclude functionally significant binding of full-length PrP C . Although our model is more aligned to the postulate that binding of the N terminus of PrP C , or cognate fragments, to phosphatidylserine may serve to consolidate or promote a neuroprotective response, we cannot exclude the possibility that the loss of membrane asymmetry may serve to attenuate or abrogate PrP C function through sequestration akin to N-terminal "tethering" (52) or perhaps indirectly such as through generic inhibition of endocytosis (67).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, aberrant N-terminal truncated forms of PrP c tethered to the cell membrane alter the response to oxidative stress and become proteaseresistant (Zeng et al, 2003). Moreover, processing of the putative N-terminal transmembrane fragment could be determinant in neurodegenerative diseases, since mice expressing a PrP variant (mutation that alters topological orientation) promote neuronal degeneration (Hegde et al, 1998;Stewart et al, 2001).…”
Section: Dissecting Prp C Domains and Cell Death: The N-terminal Domainmentioning
confidence: 99%